2011
DOI: 10.1111/j.1600-0897.2011.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Preconception CD56+16+ and/or Th1:Th2 Levels Predict Benefit from IVIG Therapy in Subfertile Women Undergoing IVF

Abstract: In subfertile women with preconception Th1:Th2 and/or % CD56(+) cell elevation, IVF success rates are low without IVIG therapy but significantly improve with IVIG therapy. In patients with normal Th1:Th2 and normal CD56(+) cell levels, IVF success rates were not further improved with IVIG therapy. IVIG may be a useful treatment option for patients with previous IVF failure and preconception Th1:Th2 and/or NK elevation. Preconception immune testing may be a critical tool for determining which patients will bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 47 publications
5
50
0
2
Order By: Relevance
“…Immunoglobulin therapy has been shown to be clinically beneficial in some selected groups of women with RPL by reducing NK cell cytotoxicity or favorably decreasing Th1/Th2 ratios (52)(53)(54). Our preliminary data revealed that the immunoglobulin therapy was effective for decreasing pregnancy loss in Sphk1…”
Section: Sphk2mentioning
confidence: 69%
“…Immunoglobulin therapy has been shown to be clinically beneficial in some selected groups of women with RPL by reducing NK cell cytotoxicity or favorably decreasing Th1/Th2 ratios (52)(53)(54). Our preliminary data revealed that the immunoglobulin therapy was effective for decreasing pregnancy loss in Sphk1…”
Section: Sphk2mentioning
confidence: 69%
“…[21][22][23] In cases where an abnormality was present, IVIG was administered at least once during the IVF cycle or at a positive pregnancy test. An additional IVIG was given during the first trimester of pregnancy and then at 4 week intervals, if these levels were still elevated following repeated monthly% CD56 + cell and/or NK cytotoxicity assessment.…”
Section: Ivig Therapymentioning
confidence: 99%
“…Such cases have often been associated with abnormalities in several different in vitro immune parameters: natural killer cell cytotoxicity, proportion of peripheral blood CD56+CD3− cells, and Th1:Th2 bias. When patients with these abnormalities are treated with immunotherapy, results have been encouraging (Carp, 2007;Clark et al, 2006;Winger et al, 2011aWinger et al, , 2011b. However, the immunological assays employed have low specificity and sensitivity (Lee et al, 2013;Thum et al, 2004).…”
Section: Introductionmentioning
confidence: 97%